Does Motility‐Restricting Fibrosis Influence Dispersal? An Experiment in Nature With Threespine Stickleback - Alexis M. Heckley; Daniel I. Bolnick; Francis Dinh; Andrew P. Hendry; Natalie C. Steinel (Ecology and Evolution)
ABSTRACT Dispersal can affect individual‐level fitness and population‐level ecological and evolutionary processes. Factors that affect dispersal could therefore have important eco‐evolutionary implications. Here, we investigated the extent to which an inflammation and tissue repair response—peritoneal fibrosis—which is known to restrict movement, could influence dispersal by conducting a mark‐recapture experiment in a lake in Alaska with threespine stickleback (Gasterosteus aculatus). A subset of captured stickleback were injected with aluminium phosphate to experimentally induce fibrosis (‘treatment group’), and another subset were injected with saline or received no injection—both of which do not induce fibrosis (‘control group’). We released all fish at one introduction point and re‐sampled stickleback throughout the lake for 8 days. We recaptured 123 individuals (n = 47 fibrosis treatment; n = 76 control) and dissected them to determine fibrosis levels. Overall, fibrosis did not affect dispersal. Some compelling (but not statistically significant) trends suggest that early‐stage inflammation may affect dispersal, providing opportunities for future work. By showing that effects on dispersal are not important side effects of fibrosis, these findings improve our understanding of the ecological implications of immune responses.